Repetitive short pulse SOS-generators; The 12th IEEE International Pulsed Power Conference, Monterey, CA, june 27-30, 1999; Vol. 2 - Lyubutin S. K.; Mesyats G. A. Gennady Andreyevich; Rukin S. N.; Slovikovsky B. G. (1999, 1999)
В фонде НТБ ТПУ отсутствует